A study on traditional roof at Melaka village case study: Kampung Morten / Izzah Lieyana Abdul Aziz - Abdul Aziz, Izzah Lieyana (2019)
Kampung Morten, where the village is in the middle of the city of Melaka. Morten village is a living museum and a lot of history about Morten village that people get to know about it. This village still practice the way of traditional Malay lifestyle. The shaped of the roof is an ‘A’ shaped, and it is connecting courtyard between main house and the kitchen. The purpose of this study is to study on a traditional rooftop at “Kampung Melaka” house where the researcher conduct a research at Kampung Morten. The intention of using the roof shape is to represent a traditional of Malacca village. By using this signage it can be a new attraction for a tourists to visit and to see the uniqueness of Kampung Morten. It is also help draw attention and differentiate landmarks and locations, advertise a promotion. The method for this study the researcher will using a qualitative method where the findings are based on observation and interview on previous research and books